Analysis of the Learning Needs of Middle School Students in Science Learning Environments in Areas with Different Technological Supports - Dewi, Pramita Sylvia; Widodo, Ari (Jurnal Pendidikan Progresif, 2024)
Analysis of the Learning Needs of Middle School Students in Science Learning Environments in Areas with Different Technological Supports. Objective: The supporting technology quality influences online learning the availability of technology in the schools varies depending on the location and the financial situation. This study aims to analyze the learning environments of schools with different technological supports. Method: Respondents were 1,543 junior high school students in grades 7, 8, and 9 who lived in six major islands of Indonesia. An online four-scale questionnaire on critical thinking in learning strategies, student involvement in teamwork, management of student learning environment, evaluation of goal setting in the learning community, cognitive problem solving, and student relevance in learning by using a Blended Learning Environment (BLE) questionnaire. Data were collected from those that have a variation in technological support. Findings: The results of this study analyze how prepared students, teachers, and schools face the conditions of the learning environment through available technology. This research can help teachers consider strategies to anticipate obstacles during learning. Conclusion: Viewed from the aspect of students, they must have good self-regulation in receiving an understanding of learning conditions. Meanwhile, teachers and schools must provide essential services in science without burdening students with tasks. Education in the era will provide an evaluation description for implementing more planned access to education in the future. Keywords: blended learning environment, technology support, science education.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202458